1978
DOI: 10.1002/pol.1978.180160508
|View full text |Cite
|
Sign up to set email alerts
|

Single crystals of cellulose II

Abstract: SynopsisRibbon-like lamellar single crystals of cellulose I1 are grown from dilute aqueous solution of cellulose triacetate (number-average degree of polymerization (DP)-15) by deacetylation and consequent precipitation. The best results are obtained with methylamine as the deacetylation reagent a t 90°C. Electron diffraction indicates the (170) planes to be the growth face. Twin growth occurs frequently with (170) as the twinning plane.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
37
0

Year Published

1979
1979
2010
2010

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 12 publications
4
37
0
Order By: Relevance
“…6c). 35,36 In the diagram, four pairs of strong diffractions (1 1 0), (1 1 0), (0 2 0), and (1 3 0) can be identified. The electron-diffraction study indicated that the lamellar crystal was cellulose II, in which the (1 1 0) planes were parallel to the long axis of the crystal.…”
Section: Analysis Of Crystalline Cellulose By Tem Electron Diffractimentioning
confidence: 97%
“…6c). 35,36 In the diagram, four pairs of strong diffractions (1 1 0), (1 1 0), (0 2 0), and (1 3 0) can be identified. The electron-diffraction study indicated that the lamellar crystal was cellulose II, in which the (1 1 0) planes were parallel to the long axis of the crystal.…”
Section: Analysis Of Crystalline Cellulose By Tem Electron Diffractimentioning
confidence: 97%
“…Other features of the diagram indicate that the (110) interference is directed perpendicular with respect to the rod direction while (020) is at a slight angle off the (110) reflection. Such orientations indicate that in the rods, the chain axes are perpendicular to the rod axis and the rods consist in elongated cellulose crystals with (110) as the growth plane as observed before in a connected study (14). In Figure 3B the orientation is decisively different as a bundle of oriented gel gives a cellulose II fiber diagram with the cellulose chain axis aligned with the axis of the strands constituting the oriented structure.…”
Section: Resultsmentioning
confidence: 76%
“…Further, electron diffraction of these products by TEM clearly showed three major diffraction rings which have typical equatorial spacings of crystalline cellulose of type II (Fig. 5) [39,40]. Discrete spots in the diffraction rings are observed, indicating high crystallinity of the products.…”
Section: Fourier Transform Infrared Spectroscopy (Ft-ir) and Transmismentioning
confidence: 94%